Internalisasi Pendidikan Pasar Modal pada Mahasiswa Jurusan Akuntansi dalam Rangka Optimalisasi Life Laboratory Program Studi Analis Keuangan - Sri Widiyati Soemodipuro; Manarotul Fatati; Th. Tyas Listyani (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2018)
The existence of Life Laboratory (The Capital Market Gallery of BEI) has not given much benefit to Accounting and Polines Department. For that reason, the acceptance of Life Laboratory's capacity by internalizing Capital Market to students must be done. The purpose of the research is to know the respondent's perception of investment in Capital Market, to know the level of literacy, to know the correlation of literacy level with demographic variables and capitalization design of Capital Market Education on Polines students. The majority of respondents' perceptions of investments in the capital market industry are positive. The level of literacy of respondents is approached with the level of knowledge about the institutional Capital Market, Capital Market products and Securities Trading. In general the level of respondents knowledge about the Capital Market is low - moderate. The research results show that there is no correlation between gender, the origin of the respondent, the level of expenditure with the level of capital market literacy. While the origin of courses and semesters associated with the level of literacy Capital Market. The capital market internalization model begins with the Capital Market school and the following stages are stocks. In the early days, new investor assistance is needed until adult investors (able to transact on their own).